(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
The quality of service is a form of the patient assessment of the level of service received. Good service is the service provided to meet the needs or expectations of patients which can lead to patient satisfaction. This study aims to determine the relationship of quality of service to patient satisfaction for users of the Health Social Insurance Administrator Agency (SIAA)/BPJS at the Midwifery Polyclinic of the Kepulauan Meranti District General Hospital which was held from December 2020 to January 2021. The type of research is a quantitative study with a cross-sectional approach. The number of samples is 98 respondents with the purposive sampling technique. The results of univariate and bivariate data analysis with the Kolmogorov-Smirnov Z test obtained a P-value of 0.111 (P> 0.005). It shows that there is no relationship between quality of service and patient satisfaction. It is hoped that the results of this study can be a reference for improving the quality of the Health Social Insurance Administrator Agency (SIAA)/BPJS at the Kepulauan Meranti District General Hospital.